Study of complications in partial nephrectomies in 1 year period at tertiary care cancer hospital - Gautam, Nischal; Nepal, Umesh; Gharti, Binod Babu; Pokhrel, Gyan Prasad; Pokhrel, Bharat Mani; Lamichhane, Nirmal (Nepalese Journal of Cancer, 2024)
Background: Incidental diagnosis of small renal masses are increasing now a days due to increased use of imaging by ultrasound or cross sectional investigations done for other reason or routine screening. This has led to evolution in management of small renal masses and changes in treatment modalities directed towards nephron sparing procedures. Partial nephrectomy has evolved from open, laparoscopic to Robotic-assisted procedures. There have been studies on laparoscopic partial nephrectomy but no studies have been done in our country and no comparison between open and laparoscopic approach. Materials and Methods: Cases who underwent partial nephrectomy from January 2021 to June 2024 were retrospectively analyzed. Altogether 46 patients underwent partial nephrectomy in open or laparoscopic surgery. The demographic data, pre-operative, per-operative and post-operative parameters were collected and tabulated. The early complications were defined as the complications that occurred during hospital stay or within 30 days of surgery. These were noted and classified according to Clavein-Dindo Classification. Data collected analyzed using SPSS 25 software. Results: We observed an overall complication rate of 49% vs 56% in laparoscopic group vs open group; In contrary, 13% vs 4.3% patients experienced high grade complications. The mortality rate was 0%. Conclusion: Laparoscopic partial nephrectomy had a steep learning curve. With maturity, the complications rates are not more than that of open surgery.